Attitude of Medical Students Towards Hospital Acquired Infections (HAIs) Prevention in a Tertiary Hospital in Jos North Local Government Area, Plateau State, Nigeria - Okonkwo, Prosper I.; Okafor, Kingsley Chinedu; Boluwatito, Bolarinwa; Garba, Joel Haruna; Kwaghal, Bitrus Salome (British Journal of Healthcare and Medical Research, 2024)
Background: The attitude of medical students and health care workers towards Hospital Acquired Infections (HAIs) is a fundamental step towards implementation of the infection control protocols. These infections are acquired illnesses that are usually not present or incubating when a patient is admitted. This study seeks to assess the attitude of medical students towards Hospital Acquired Infections (HAIs) prevention in a Tertiary Hospital in Jos North Local Government Area, Plateau State, Nigeria. Methods: This was a descriptive cross-sectional study done between June and November 2019 among medical students using a Multistage sampling technique. Data was collected using a self-administered structured questionnaire and analyzed using the IBM SPSS 28 (Statistical Package for the Social Sciences). Results: The majority (98.2%) of the medical students agree that it is important to remove blood spillages quickly, and change of linens and clothes when soiled. Concerning periodic cleaning of walls and floors with disinfectants, 98.2% consider this to be important, while 0.5% do not and 1.4% do not know. As regards the quick disposal of used syringes and needles, 98.6% see this as important, while 1.4% do not. Regarding the importance of instrument sterilization for infection control, 97.7% said it is important, 95.5% considered the habit of hand washing between patients by health workers as important, 3.2% don’t know and 0.5 said it is not important. A high proportion (84.5%) of students were willing to adopt the HAI prevention methods, 11.4% were undecided and 4.1% were unwilling. One in twenty (19.6%) were not decided about championing the promotion of HAI in the hospital, 3.7% were unwilling to be HAI ambassadors, 76.7% agreed to help promote the need for HAI prevention. Conclusion: Generally, majority of students had a positive attitude (91.8%) toward HAI prevention while 8.2% had negative attitude. This is a foundation for championing the spread of the message and monitoring compliance with the standard precautions and existing protocol for HAI prevention.